RELATIONSHIP BETWEEN TOTAL CHLOROPHYLL AND PHYTOPLANKTON INDIVIDUALS OF ROSETTA BRANCH OF RIVER NILE, EGYPT - Shaaba, A. M.; Mansour, H. A.; Sabera, A. A.S. (Ecoprint: An International Journal of Ecology, 2013)
Total chlorophyll concentrations of the phytoplanktonic samples of Rosetta branch of the River Nile at the stations before Edfina barrage (from station I to V) and after Edfina barrage (stations VI and VII) were studied during two successive years from August 2006 to April 2008. At all stations, the total chlorophyll contents of the identified algae and the maximum quantitative algal individuals were found maximum during summer 2007. Peak periods of total chlorophyll coincided with peak periods of the stations that recorded high algal biomass. Phytoplankton in Rosetta branch of the river Nile at the most studied stations (I, II, IV, V and VI) had chloro-character particularly in summer 2007. A positive correlation was observed between the fluctuations of total chlorophyll contents of the phytoplankton and those of total number of individuals at all investigated stations of Rosetta branch. DOI: http://dx.doi.org/10.3126/eco.v18i0.9392 Ecoprint: An International Journal of Ecology Vol. 18, 2011 Page: Uploaded date: 12/20/2013